2018
DOI: 10.1016/j.jecp.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

When it is apt to adapt: Flexible reasoning guides children’s use of talker identity and disfluency cues

Abstract: An eye-tracking methodology was used to examine whether children flexibly engage two voice-based cues, talker identity and disfluency, during language processing. Across two experiments, 5-year-olds (N = 58) were introduced to two characters with distinct color preferences. These characters then used fluent or disfluent instructions to refer to an object in a display containing items bearing either talker-preferred or talker-dispreferred colors. As the utterance began to unfold, the 5-year-olds anticipated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
(38 reference statements)
2
9
0
Order By: Relevance
“…Our study provides an important contribution to the literature on children's predictive use of disfluencies, which had previously been limited to studies of monolingual English-learning children (Kidd et al, 2011;Orena & White, 2015;Owens & Graham, 2016;Owens et al, 2018;Thacker, Chambers, & Graham, 2018). We replicated these findings with English monolinguals, and extended them to French monolinguals and French-English bilinguals.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Our study provides an important contribution to the literature on children's predictive use of disfluencies, which had previously been limited to studies of monolingual English-learning children (Kidd et al, 2011;Orena & White, 2015;Owens & Graham, 2016;Owens et al, 2018;Thacker, Chambers, & Graham, 2018). We replicated these findings with English monolinguals, and extended them to French monolinguals and French-English bilinguals.…”
Section: Discussionsupporting
confidence: 65%
“…Subsequent research has extended this work to show that children's predictive use of speech disfluencies is robust with previously reliable speakers, but not with previously unreliable speakers (Orena & White, 2015). Disfluencies may also provide cues to children about a speaker's preference for particular objects (Thacker, Chambers, & Graham, 2018). Additionally, three-year-olds can use disfluencies to predict that a speaker will label an object that is perceptually familiar but novel to the discourse (e.g., a familiar object that has not previously been mentioned; Owens & Graham, 2016).…”
mentioning
confidence: 87%
“…In contrast, children did not use speech fluency cues to revise their hypotheses when forming referential predictions. This finding was somewhat surprising, given that recent research has demonstrated that 5-year-old children can indeed engage these same two cues during language processing in other contexts ( Thacker et al, 2018 ). However, an important difference between these two paradigms is that in Thacker et al (2018) the referents were familiar, whereas the present study used novel objects and labels.…”
Section: Discussionmentioning
confidence: 89%
“…This finding was somewhat surprising, given that recent research has demonstrated that 5-year-old children can indeed engage these same two cues during language processing in other contexts ( Thacker et al, 2018 ). However, an important difference between these two paradigms is that in Thacker et al (2018) the referents were familiar, whereas the present study used novel objects and labels. If disfluencies in the present study signaled that the talker was likely to refer to the unfamiliar-to-them object (i.e., the talker-non-preferred object), then it is understandable that children did not use the disfluency cue, as this result then echoes previous findings suggesting that children of this age do not associate disfluency with unfamiliarity alone ( Owens et al, 2017 ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation